The emerging gender morphemes (-x and -e) and their approach in spanish press - Cabello Pino, Manuel (Círculo de Lingüística Aplicada a la Comunicación, 2022)
ince 2017, a new phenomenon has attracted great attention of the Spanish press that has led to a revolution in the way of understanding the issue of inclusive language: we refer to the popularization of “emerging gender morphemes”: –x and –e. The objectives of this work are, in the first place, to determine if any evolution is perceived in the way in which the Spanish digital press has presented this phenomenon. Second, to analyze whether or not the arguments made in the press to support or reject these new resources are the same as those that have usually been used with the traditional alternatives to the generic masculine. And, thirdly, to check if the rejection of them is generalized between the ideological position that has always rejected inclusive language and if the defenders of the resources of the more traditional inclusive language also support these new alternatives to the generic masculine.
Keywords: linguistic sexism; inclusive language; linguistic attitudes; gramatical gender; morpheme -e